Chapter Il progetto bioregionale dell'Île-de-France: una proposta per la ricomposizione ecoterritoriale della Grande Parigi - Sinai, Agnès (Territori, 2023)
In the face of the disproportionate "Greater Paris" operation and its unreasonable rhetoric, the "Biorégion Île-de-France 2050" vision tries to anticipate in project a trend already underway in things: namely, the disintegration of the colossal metropolitan agglomeration of Paris, collapsing on its fragile metabolic roots due to the increasing unsustainability of the long chains on which it has thrived. The aim is to convey this movement into a recomposition of the Capital's territory into eight bioregions, interconnected by synergetic, reticular and non-hierarchical relations in the name of local self-sustainability: the chapter describes this thought experiment that is also a concrete eco-territorialist proposal.